Application of linear programming model for optimizing the components of combined photovoltaic and battery system - Lale Mohamadifar; Seyed Hamed Moosavirad; Mitra Mirhosseini (مدیریت مهندسی و رایانش نرم)
In this article, a combined energy system independent of the national power grid, including solar panels and batteries, is used as a storage system to provide energy. Due to the high costs of the system components, optimization with linear programming aims to reduce costs systems and complete coverage of energy demand has been done and the model has been implemented for 2 cities of Kerman and Mashhad. The results showed that since the output power of the photovoltaic panel is dependent on the temperature and intensity of solar radiation, under the conditions of using the same components and demand Equally, the implementation of this system in Kerman is more cost-effective. The sensitivity analysis of the studied system has been carried out and its effect has been examined in the results.